1985
DOI: 10.1177/001698628502900206
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Loneliness in the Gifted Adolescent

Abstract: Gifted adolescents reported degree of loneliness to be a function of anger, depression, and stressful life changes. Furthermore, the most salient aspects of depression for predicting loneliness were helplessness, social introversion, and low self-esteem. The relationship between loneliness and depression suggests further evidence of a possible success depression in certain gifted adolescents. The results help to clarify the complex relationship between loneliness and other dysphoric states in these youths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 20 publications
0
27
0
2
Order By: Relevance
“…(Peterson et al, 2009, p. 40). Loneliness in gifted students has also been recognized in combination with depression and anger (Kaiser & Berndt, 1985). In this study, one in eight of the gifted participants reported significant levels of loneliness, depression, and anger.…”
Section: Relationships With Classmates (Sense Of Belonging)mentioning
confidence: 62%
See 1 more Smart Citation
“…(Peterson et al, 2009, p. 40). Loneliness in gifted students has also been recognized in combination with depression and anger (Kaiser & Berndt, 1985). In this study, one in eight of the gifted participants reported significant levels of loneliness, depression, and anger.…”
Section: Relationships With Classmates (Sense Of Belonging)mentioning
confidence: 62%
“…Since academically gifted students in this study are reporting same or higher levels of belonging, the feeling of fitting into a group within the classroom is present and thus these students are not experiencing school as marginalizing. Loneliness in gifted students has also been previously identified in gifted students (Kaiser & Berndt, 1985) as part of disharmony theory. However, the results in this study support the contrary.…”
Section: Sense Of Belongingmentioning
confidence: 87%
“…Various theories (Blatt, 1995;Delisle, 1986;Dixon & Scheckel, 1996;Kaiser & Berndt, 1985;Piechowski, 1979) about characteristics of the gifted have suggested that this population has a higher risk of suicide than their average peers. However, the literature base directly concerned with the topic of suicide among gifted adolescents is filled with much conjecture rather than empirically sound research.…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics include: unusual sensitivity and perfectionism (Delisle, 1986), isolationism related to extreme introversion (Kaiser & Berndt, 1985), and overexcitabilities identified by Dabrowski. Dixon and Scheckel (1996) described the five overexcitabilities identified by Dabrowski and reiterated by Piechowkski (1979) as: "psychomotor (e.g., fast games and sports, acting out, impulsive actions), sensual (e.g., sensory pleasure, sexual overindulgences), intellectual (e.g., introspection, avid reading, curiosity), imaginational (e.g., fantasy, animistic and magical thinking, mixed truth and fiction, illusions), and emotional (e.g., strong affective memory, concern with death, depressive and suicidal moods, sensitivity in relationships, feelings of inadequacy and inferiority)" (p. 389).…”
Section: Literature On Suicide Among Gifted Studentsmentioning
confidence: 99%
“…Does the poor achievement cause the poor self concept, or does the poor self concept result in poor achievement? For example, Kaiser & Berndt (1985) sought indicators that were predictors of loneliness in the gifted adolescent. In studying summer Governor's school junior and senior high school students, ages 14-17, they concluded that the majority of gifted adolescents are exceptionally well-adjusted and find their success goes hand in hand with a healthy self confidence and self esteem.…”
Section: Underachieversmentioning
confidence: 99%